Aflatoxin biosynthesis regulators AflR and AflS : DNA binding affinity, stoichiometry, and kinetics - Abbas, Asmaa; Prajapati, Ranjit K; Aalto-Setälä, Emil; Baykov, Alexander A.; Malinen, Anssi M (Portland Press, 2025)
Aflatoxins, potent foodborne carcinogens produced by Aspergillus fungi, pose significant health risks worldwide and present challenges to food safety and productivity in the food chain. Novel strategies for disrupting aflatoxin production, cultivating resilient crops, and detecting contaminated food are urgently needed. Understanding the regulatory mechanisms of aflatoxin production is pivotal for targeted interventions to mitigate toxin accumulation in food and feed. The gene cluster responsible for aflatoxin biosynthesis encodes biosynthetic enzymes and pathway-specific regulators, notably AflR and AflS. While AflR, a DNA-binding protein, activates gene transcription within the cluster, AflS enhances aflatoxin production through mechanisms that are not fully understood. In this study, we developed protocols to purify recombinant AflR and AflS proteins and utilised multiple assays to characterize their interactions with DNA. Our biophysical analysis indicated that AflR and AflS form a complex. AflS exhibited no DNA binding capability on its own but unexpectedly reduced the DNA binding affinity of AflR. Additionally, we found that AflR achieves its binding specificity through a mechanism in which either two copies of AflR or its complex with AflS bind to target sites on DNA in a highly cooperative manner. The estimated values of the interaction parameters of AflR, AflS and DNA target sites constitute a fundamental framework against which the function and mechanisms of other aflatoxin biosynthesis regulators can be compared.